2020
DOI: 10.1088/2515-7647/ab9072
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study of shockley-read-hall and radiative recombination in GaN on Al2O3, freestanding GaN, and GaN on Si

Abstract: Here we study and correlate structural, electrical, and optical properties of three GaN samples: GaN grown by metalorganic chemical vapor deposition on sapphire (GaN/Al2O3), freestanding GaN crystals grown by the high nitrogen pressure solution method (HNPS GaN), and GaN grown by hydride vapor phase epitaxy on silicon (GaN/Si). Defect and impurity densities and carrier concentrations are quantified by x-ray diffraction, secondary mass ion spectroscopy, and Hall effect studies, respectively. Power-dependent pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
3
11
0
Order By: Relevance
“…As mentioned earlier, nitrogen doping regulates the property of graphene by maintaining good conductivity and carrier mobility 31 . The obtained mobility value is higher than that of the standard mobility value of GaN and also falls within the mobility range for nitrogen doped SLG as reported in literature 46,72 . The hall measurement data corroborate with I-V results.…”
Section: Surface Composition Analysissupporting
confidence: 83%
“…As mentioned earlier, nitrogen doping regulates the property of graphene by maintaining good conductivity and carrier mobility 31 . The obtained mobility value is higher than that of the standard mobility value of GaN and also falls within the mobility range for nitrogen doped SLG as reported in literature 46,72 . The hall measurement data corroborate with I-V results.…”
Section: Surface Composition Analysissupporting
confidence: 83%
“…Meyer et al [41] and Ščajev et al [42] studied carrier lifetimes using temperature-dependent time-resolved photoluminescence. Meyer et al studied SRH recombination in MOVPE grown GaN layers on a Si substrate [N dis ¼ (5.6 AE 0.1)Â10 10 cm À2 ], a sapphire substrate (N dis ¼ 2.9 Â 10 8 cm À2 ), and a freestanding GaN substrate grown by the high nitrogen pressure solution method [N dis ¼ (2.8 AE 0.1)Â10 7 cm À2 ].…”
Section: Bulk Nonradiative Recombination Current Density Of Gan P þ N...mentioning
confidence: 99%
“…Meyer et al studied SRH recombination in MOVPE grown GaN layers on a Si substrate [N dis ¼ (5.6 AE 0.1)Â10 10 cm À2 ], a sapphire substrate (N dis ¼ 2.9 Â 10 8 cm À2 ), and a freestanding GaN substrate grown by the high nitrogen pressure solution method [N dis ¼ (2.8 AE 0.1)Â10 7 cm À2 ]. [41] Ščajev et al, in contrast, studied the ambipolar lifetime τ a in 1À3 Â 10 16 cm À3 doped HVPE n-GaN layers (N dis ¼ 0.14À1.3 Â 10 8 cm À2 ) under high excitation conditions (pÀN d ¼ 0.1À5 Â 10 19 cm À3 ). [42] As τ a is expressed from charge neutrality as…”
Section: Bulk Nonradiative Recombination Current Density Of Gan P þ N...mentioning
confidence: 99%
“…The value of τ 0 depends strongly on the threading dislocation density as a result of the heteroepitaxial growth of GaN on non-native substrates, as well as point defect (i.e., vacancy and impurity) concentration, which is subject to material growth chemistry and conditions. The non-radiative carrier lifetime in GaN on Al 2 O 3 (Si) grown via metalorganic chemical vapor deposition (MOCVD) is reported to be ≈ 400 ps (250 ps) at room temperature in [23]. The power-dependent photoluminescence measurements showed a strong yellow luminescence (YL) at 2.25 eV in both GaN on Al 2 O 3 and GaN on Si samples.…”
Section: A Fundamental Modeling Equationsmentioning
confidence: 99%
“…The power-dependent photoluminescence measurements showed a strong yellow luminescence (YL) at 2.25 eV in both GaN on Al 2 O 3 and GaN on Si samples. The YL band was attributed to V Ga and C N -related defects [23]. In [24], it was shown that for GaN epilayers deposited on high-quality AlN buffer grown on sapphire using migrationenhanced MOCVD, τ 0 ≈ 2 ns at room temperature.…”
Section: A Fundamental Modeling Equationsmentioning
confidence: 99%